The role of moderate-to-vigorous physical activity in mediating the relationship between central adiposity and immunometabolic profile in postmenopausal women - Diniz, Tiego A. [UNESP]; Rossi, Fabricio E. [UNESP]; Silveira, Loreana S. [UNESP]; Neves, Lucas Melo; de Souza Fortaleza, Ana Claudia [UNESP]; Christofaro, Diego G. D. [UNESP]; Lira, Fabio S. [UNESP]; Freitas-Junior, Ismael F. [UNESP] (Archives of Endocrinology and Metabolism, 2017)
Objectives: To analyze the role of moderate-to-vigorous physical activity (MVPA) in mediating the relationship between central adiposity and immune and metabolic profile in postmenopausal women. Materials and methods: Cross-sectional study comprising 49 postmenopausal women (aged 59.26 ± 8.32 years) without regular physical exercise practice. Body composition was measured by dual-energy X-ray absorptiometry. Fasting blood samples were collected for assessment of nonesterified fatty acids, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), adiponectin, insulin and estimation of insulin resistance (HOMA-IR). Physical activity level was assessed with an accelerometer (Actigraph GTX3x) and reported as a percentage of time spent in sedentary behavior and MVPA. All analyses were performed using the software SPSS 17.0, with a significance level set at 5%. Results: Sedentary women had a positive relationship between trunk fat and IL-6 (rho = 0.471; p = 0.020), and trunk fat and HOMA-IR (rho = 0.418; p = 0.042). Adiponectin and fat mass (%) were only positively correlated in physically active women (rho = 0.441; p = 0.027). Physically active women with normal trunk fat values presented a 14.7% lower chance of having increased HOMA-IR levels (β [95%CI] = 0.147 [0.027; 0.811]). Conclusions: The practice of sufficient levels of MVPA was a protective factor against immunometabolic disorders in postmenopausal women.
Keywords: Adiponectin; Adipose tissue; Cytokines; Insulin resistance; Obesity; Postmenopause